The Implementation of Higher Order Thinking Skill (HOTS) in Junior High School: Teaching Practice and Problems - Feronica, Rani Ayu; Apriani, Eka; Edy, Sarwo (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study is aims to find out teaching practice and problems in impelementing HOTS. This research is descriptive qualitative. Subject of this study were four English Teacher in SMPN 1 Rejang Lebong. Questionnaire and interview were used to find out data of this research. Data analyzed by using qualitative analysis. The result of this study is (1) the implementation of HOTS in SMPN 1 Rejang Lebong is well done based on Anderson Taxonomy: remembering, understanding, applying, analyzing, evaluating, and creating. Second, teaching problems in HOTS implementation, and (2) lack of facilities, lack of time, lack of training, lack of knowledge, lack of connection, and lack of motivation were teaching problems of HOTS implementation. This finding is hoped can be used to know about teaching and learning process by using HOTS in junior high school.Keywords: HOTS, Junior High School, Teaching Practice, Teaching Problems